2018
DOI: 10.1515/humo-2017-0010
|View full text |Cite
|
Sign up to set email alerts
|

Strength training with vascular occlusion: a review of possible adaptive mechanisms

Abstract: Strength training with blood flow restriction, or KAATSU training, has been shown to be as effective as conventional strength training to promote muscular strength and hypertrophy. Several mechanisms have been suggested as hypotheses to explain the adaptations arising from this training method. Among these is metabolic stress, which exerts important physiological effects and may influence the training adaptations in question. In addition, hypoxia produced by the technique may change the neural recruitment patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 84 publications
0
13
0
5
Order By: Relevance
“…There is evidence that anaerobic conditions induce the glycolytic rate during exercise and HIF-1 (hypoxia inducible factor-1) facilitates the expression of glycolytic genes that encode phosphofructokinase (PFK), a key enzyme in glycolysis. This contributes to an increase in muscle glycolytic capacity [56][57][58][59][60]. Summer matter et al [61] indicated that interval training increased the number of LA transporters: monocarboxylate transporter-1 (MCT-1) and MCT-4.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that anaerobic conditions induce the glycolytic rate during exercise and HIF-1 (hypoxia inducible factor-1) facilitates the expression of glycolytic genes that encode phosphofructokinase (PFK), a key enzyme in glycolysis. This contributes to an increase in muscle glycolytic capacity [56][57][58][59][60]. Summer matter et al [61] indicated that interval training increased the number of LA transporters: monocarboxylate transporter-1 (MCT-1) and MCT-4.…”
Section: Discussionmentioning
confidence: 99%
“…Kettlebell lifting takes the leading place among those kinds of sport and it has a positive influence on the cadets' organism [7,8,16]. In scientific publications [17,18,19,20] it is proved that power exercises contribute to aesthetic selfimprovement due to the proportionality and symmetry of the muscles and the allbalanced development of all muscle groups, body correction, including elimination of disadvantages in it, recovery after injuries, increase in ability to work, and the formation of a harmonious figure. Scientists [21,22] point out that power loads have a positive effect on the state of health, ability to work and a range of physical and psychological qualities.…”
Section: Discussionmentioning
confidence: 99%
“…The training method BFR is characterized by the restriction / manipulation of the blood flow to and away from the limbs due to the application of elastic straps or inflatable pressure cuffs (e.g., blood pressure cuffs) to the proximal portion of the limbs (see Figure 1 A,B) [ 117 , 125 , 127 , 128 , 129 , 130 ]. The manipulation of the blood flow especially decreases the venous return, which increases the accumulation of metabolites in the muscle triggering pronounced adaptational processes [ 117 , 125 , 127 , 128 , 129 , 130 ]. A particular type of BFR is KAATSU where special inflatable cuffs with pressure sensors are used [ 131 ].…”
Section: Resistance Training With Blood Flow Restriction—an Added mentioning
confidence: 99%